Invasive Candida pneumonia, in association with Candida esophagitis and gastritis, in a presumably immunocompetent patient - Devon Jackson,; Lamarque Coke,; Kamilah Fernandez,; Kathriel Brister, (Autopsy and Case Reports, 2023)
Candida pneumonia remains a difficult diagnosis and is most common in immunocompromised individuals. It has been rarely reported in immunocompetent individuals. We present a case of unsuspected Candida pneumonia associated with Candida esophagitis and gastritis discovered on postmortem examination in a presumably immunocompetent patient. The patient was a 71-year-old male who presented with chest pain and was subsequently found to have a myocardial infarction treated with angioplasty and drug-eluting stent placement. The patient’s recovery was complicated by pneumonia refractory to antibiotics, and he went on to experience acute hypoxic respiratory failure, sepsis, disseminated intravascular coagulation (DIC), and ultimately expired. Autopsy revealed evidence of myocardial infarction as well as unsuspected Candida albicans pneumonia, esophagitis, and gastritis. Our case highlights how a presumably immunocompetent individual can develop this infection and how Candida esophagitis and Candida gastritis can be seen in association with Candida pneumonia. Due to the difficulty in diagnosing Candida pneumonia antemortem, autopsies provide a key opportunity to better understand these cases and the factors that may contribute to their development.